2021
DOI: 10.1111/ejn.15258
|View full text |Cite
|
Sign up to set email alerts
|

Basal ganglia and cortical control of thalamic rebound spikes

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 64 publications
(135 reference statements)
0
3
0
Order By: Relevance
“…These processes can occur through feedforward or feedback recurrent circuits between the cortex and thalamus and can be the underlying mechanisms of attention and goal-directed behavior (55,56). In addition, neuronal hyperpolarization in the VPL region is known to trigger activation of hyperpolarization-activated cyclic nucleotide-gated (HCN) channels and the occurrence of rebound spike-burst firing of thalamocortical neurons in the thalamus-cortex recurrent loop (57)(58)(59).…”
Section: Forelimb Sensory Pathways Revealed By Diana Fmrimentioning
confidence: 99%
“…These processes can occur through feedforward or feedback recurrent circuits between the cortex and thalamus and can be the underlying mechanisms of attention and goal-directed behavior (55,56). In addition, neuronal hyperpolarization in the VPL region is known to trigger activation of hyperpolarization-activated cyclic nucleotide-gated (HCN) channels and the occurrence of rebound spike-burst firing of thalamocortical neurons in the thalamus-cortex recurrent loop (57)(58)(59).…”
Section: Forelimb Sensory Pathways Revealed By Diana Fmrimentioning
confidence: 99%
“…These bursts are enhanced and linked to motor dysfunction in SPR-knockout mice, which are dopamine-deficient due to defects in tetrahydrobiopterin synthesis (Kim et al, 2017). Furthermore, models suggest that synchronous BG output is especially effective at generating rebound bursting (Nejad et al, 2021).…”
Section: Bg-thalamic Interactions In Health and Parkinsonismmentioning
confidence: 99%
“…In the central nervous system, the inhibitory synapse transmission may induce excitatory signals via RF. 10,[14][15][16]30,31 Although RF was elicited in vitro 14,30,31 or in vivo from isoflurane-anaesthetized adult mice, 32 however, Alviña et al found that intact mouse or rat deep cerebellar nuclei neurons rarely show RF under physiological conditions in vivo, 33 implying RF may not be observed in awake behaving intact animals but is most likely to contribute to neural hyperexcitability under pathophysiological condition. In PNS, different from central neuron, DRG neurons do not receive synapse transmission, but there are a variety of receptors on DRG neurons.…”
mentioning
confidence: 99%